Subjective well-being and income: A compromise between Easterlin paradox and its critiques - Rusen Yasar (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
Despite rising popularity of subjective well-being (SWB) as a proxy for utility, its relationship with income is still unresolved. Against the background of debates around the 'Easterlin paradox', this paper seeks a compromise between two positions: one that insists on individual relative income, and one that finds similarity between individual and aggregate levels. Proposing a model which puts the emphasis on the interaction between individual and aggregate-level factors, it argues that the effect of relative income on SWB varies across countries as a function of average income, in addition to a relatively small direct effect of the latter, in partial agreement with the two major positions. The model is tested crosssectionally on the data from the latest wave of World Values Survey. The results from hierarchical mixed-effect models confirm the main argument. But further examination reveals that there is still unaccounted variation especially in middle-income economies.
Keywords: D31; C31; 330; subjective well-being; Easterlin paradox; relative income; national income